2013
DOI: 10.5472/mmj.2013.02956.0
|View full text |Cite
|
Sign up to set email alerts
|

Non Immune Hydrops Fetalis; Two Premature Infants with Favorable Outcome

Abstract: Non immune hydrops fetalis is defined as the excessive accumulation of fluid in two or more compartments of the fetus in the absence of any maternal-fetal blood incompatibility. The clinical presentations include ascites, scalp edema, pleural or pericardial effusions and polyhydramnios. Perinatal mortality in this severe clinical condition is high, between 50-98%. Prematurity is an important risk factor for mortality. Despite many advances in diagnosis, therapy and ventilation management during the last decade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Fetal atrial flutter is the more common tachyarrhythmia and is responsible for up to 25 % of fetal tachyarrhythmias [21]. The incidence of NIHF in fetal SVT is bet ween 35-60 % [7]. In the retro spective analysis of 127 cases of fetal tachyarrhythmia by Simpson and Sharland [22], SVT was found in 105 patients and atrial flutter in 22 cases, and 52 (40.9 %) cases were hydropic.…”
Section: Cardiac Dysrhythmiasmentioning
confidence: 99%
See 3 more Smart Citations
“…Fetal atrial flutter is the more common tachyarrhythmia and is responsible for up to 25 % of fetal tachyarrhythmias [21]. The incidence of NIHF in fetal SVT is bet ween 35-60 % [7]. In the retro spective analysis of 127 cases of fetal tachyarrhythmia by Simpson and Sharland [22], SVT was found in 105 patients and atrial flutter in 22 cases, and 52 (40.9 %) cases were hydropic.…”
Section: Cardiac Dysrhythmiasmentioning
confidence: 99%
“…The baby required adenosine treat ment after birth and was on regular digoxin and flecainide. Kayiran et al [7] reported a fetus developed Wolff-Parkinson-White syn drome with recurrent paroxysmal tachycardia (300 beats/min) and with hydrops fetalis after 30 weeks' gestation. Postnatal adenosi ne followed by oral digoxin (6 μg/kg/day) and propranolol (2 mg/ kg/day) ensured a favorable recovery.…”
Section: Cardiac Dysrhythmiasmentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence of NIHF in fetal supraventricular tachycardia is between 35-60%. (10) Antenatal ultrasound scan permits the detection, monitoring and often helps to determine the cause of hydrops foetalis. (11) Advances in ultrasonography (pulsed Doppler, colour Doppler, power Doppler) have made the diagnosis of these defects possible early in gestation.…”
Section: Introductionmentioning
confidence: 99%